Myocardial infarction detection using ECG signal applying deep learning techniques - ConvNet, VGG16, InceptionV3 and MobileNet - Promita, Samanta Tabassum; Biswas, Simon Abhijet; Mozumder, Nisat Islam; Taharat, Mamur (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.